INOVASI PEMBELAJARAN TEMATIK DALAM MENINGKATKAN KETERAMPILAN DASAR SISWA DI SDN 2 LABUAN KANANGA - Marjan, Marjan; Trimansyah, Trimansyah; Idhar, Idhar (Prodi PAI STIT Sunan Giri Bima, 2024)
This study aims to describe the implementation of instructional innovations carried out by teachers at SDN 2 Labuan Kananga in improving students’ basic skills. As thematic or integrated learning has been applied in almost all schools, the implementation of thematic learning becomes one of the approaches that is relevant to students’ needs in developing skills such as reading, arithmetic, listening, and speaking. This is important because basic skills serve as a foundation that supports students’ success at the next level of education. The common problem that often arises in the classroom is the lack of students’ learning interest, which is influenced by monotonous and less innovative teaching methods. Teachers who do not present variation in teaching tend to make students passive, thus making the learning process less effective. Through thematic learning, teachers have the opportunity to connect learning materials with students’ real-life experiences, making the learning process more contextual, enjoyable, and meaningful.